Efektivitas Pembelajaran Dengan Assesmen Berbasis Kahoot! Terhadap Motivasi Belajar Fisika Mahasiswa Tadris IPA - Riris Idiawati; Khoironi Fanana Akbar; Hilya Wildana Sofia; Anis Wildatus Saqinah (International Forum of Researchers and Lecturers, 2024)
The focus of the problem in this research is the low motivation of students in learning physics. This research is a quantitative study using pre-experiment method, where the research design is one group design pre-test post-test. The sample of this study consisted of 32 students of Tadris IPA KH.Muhtar Syafaat University Blokagung Banyuwangi (UIMSYA). The results showed pretest data on students' physics learning motivation, namely with an average value of 102.13.average value of 102.13 is in the medium category. While the results of the post-test data obtained were 126.50 in the very high category. The N-gain score test results show a value of 0.5 in the medium category. This shows that the use of Kahoot! based assessment is very effective in increasing the physics learning motivation of Tadris IPA UIMSYA students. The results of this study are expected to be one of the innovations in scientific learning, especially physics courses so that students are not easily bored and much more active in learning.